2019
DOI: 10.1103/physrevb.99.245409
|View full text |Cite
|
Sign up to set email alerts
|

Weyl semimetals in ultrafast laser fields

Abstract: We study theoretically interaction of topological Weyl semimetals with an ultrafast optical pulse. The electron dynamics in such material is coherent and highly anisotropic. For some directions of pulse polarization, the electric dynamics is irreversible, which means that the residual electron conduction band population after the pulse is comparable to the maximum conduction band population during the pulse. For other directions of polarization, the electron dynamics is highly reversible and, after the pulse, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A better representation of the detected sign change is shown in Figure b, where the modulation at the temporal overlap ( t = 0 fs) for each probe wavelength is displayed. Recent theoretical calculations of WSM's in ultrafast laser fields [ 47 ] predicted that the fast electron–electron scattering toward the Weyl node happens in the first 10 fs after the pump pulse arrives. Even though this is at the limit of the temporal resolution of the experimental setup, we attribute the sharp peak at the temporal overlap in Figure 3a,b to this ultrafast relaxation, visible in the single traces at selected 715 and 785 nm probe wavelengths in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…A better representation of the detected sign change is shown in Figure b, where the modulation at the temporal overlap ( t = 0 fs) for each probe wavelength is displayed. Recent theoretical calculations of WSM's in ultrafast laser fields [ 47 ] predicted that the fast electron–electron scattering toward the Weyl node happens in the first 10 fs after the pump pulse arrives. Even though this is at the limit of the temporal resolution of the experimental setup, we attribute the sharp peak at the temporal overlap in Figure 3a,b to this ultrafast relaxation, visible in the single traces at selected 715 and 785 nm probe wavelengths in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…These results will be interesting for the investigation of the role of electronic decoherence, which is crucial for petahertz light-field information technology. In addition, the concept of light-field driven electrons has recently found attraction to investigate topological effects in gapped materials such as TMDCs using circular polarized driving pulses [57][58][59], which might become particularly interesting for Coulomb engineering of band gap materials [60].…”
mentioning
confidence: 99%
“…We have shown that the topological resonance can be observed as a large conduction band population in some regions in the reciprocal space for two dimensional topological materials, such as gapped graphene-like materials or TMDCs, when these materials are placed in a circularly polarized pulse [10,17]. The topological resonance can be also realized in 3D topological solids such as Weyl semimetals in the field of a circularly polarized pulse [18]. The topological resonance is determined by nontrivial properties of Berry connections and the accumulation of the topological phase depends on the sign of the corresponding Berry curvature.…”
Section: Introductionmentioning
confidence: 94%